2011
DOI: 10.1038/nmeth.1742
|View full text |Cite
|
Sign up to set email alerts
|

A scalable pipeline for highly effective genetic modification of a malaria parasite

Abstract: In malaria parasites the systematic experimental validation of drug and vaccine targets by reverse genetics is constrained by the inefficiency of homologous recombination and by the difficulty of manipulating adenine and thymine (AT) rich Plasmodium DNA in E. coli. We overcome these roadblocks by demonstrating that a high integrity library of P. berghei genomic DNA (>77% AT) in a bacteriophage N15-based vector can be modified efficiently using the lambda Red method of recombineering. We built a pipeline for ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 95 publications
(129 citation statements)
references
References 33 publications
2
122
0
Order By: Relevance
“…We have shown that this result can readily be achieved with our human-adapted clone, using the nonessential p230p gene to target integration into the genome. Recombination efficiencies are highly dependent on the identity and length of the targeting regions used, and increased targeting sequence length has been demonstrated to improve recombination efficiency by up to 10-fold in P. berghei (27). We therefore anticipate that further increases in integration efficiency are likely with improvements in transfection construct design, such as use of the recently described pJAZZ vector-based recombineering approach to produce linear malarial transfection constructs with long homology arms (27).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that this result can readily be achieved with our human-adapted clone, using the nonessential p230p gene to target integration into the genome. Recombination efficiencies are highly dependent on the identity and length of the targeting regions used, and increased targeting sequence length has been demonstrated to improve recombination efficiency by up to 10-fold in P. berghei (27). We therefore anticipate that further increases in integration efficiency are likely with improvements in transfection construct design, such as use of the recently described pJAZZ vector-based recombineering approach to produce linear malarial transfection constructs with long homology arms (27).…”
Section: Discussionmentioning
confidence: 99%
“…The Pearson's correlation coefficient (PCC) was obtained using the Coloc2 plugin from Fiji (65) P. berghei culturing and genetic manipulationIntra-erythrocytic asexual stages of P. berghei ANKA (procured from MR4) were maintained in BALB/c mice. For the generation of the knockout construct and for the transfection of parasites, established procedures were followed (66,67). All transfection experiments were performed twice.…”
Section: Complementation Of Fh Deficiency In ∆Fumacb Strain With Pffhmentioning
confidence: 99%
“…The integration cassette was released as a linear fragment by an ApaI/BamHI digest. For independent confirmation of the phenotype, a third mutant clone was created using a gex1 deletion vector from the PlasmoGEM resource (Pfander et al 2011) with the design number PbGEM-45681 (see http://plasmogem. sanger.ac.uk for details of vector design).…”
Section: P Berghei Genetic Modificationmentioning
confidence: 99%